Development and validation of an LC-MS/MS method for the simultaneous estimation of tadalafil and macitentan in rat plasma: Greenness assessment and design of experiment approach - Sravanthi Gandu; Kumaraswamy Gandla; Lalitha Repudi (Green Analytical Chemistry)
This study presents the development and validation of a sensitive LC-MS/MS method for the simultaneous quantification of tadalafil and macitentan in rat plasma, enabling detailed pharmacokinetic profiling following single-dose administration. Optimization of critical parameters, including organic phase composition (50% acetonitrile), flow rate (1.0 mL/min), and pH (3.2), was achieved using a Box-Behnken Design, ensuring accurate separation and quantification. The retention times were 4.13 min for tadalafil, 5.32 min for macitentan, and 7.89 min for the internal standard, ritonavir. The method adhered to regulatory validation guidelines, linearity was observed over a concentration range of 20 to 400 ng/mL for tadalafil and 5 to 100 ng/ml for macitentan, yielding correlation coefficients of 0.9997 and 0.9998, respectively, with limits of quantitation (LOQs) of 19.10 ng/mL for tadalafil and 4.21 ng/mL for macitentan. Precision, expressed as %CV, was consistently below 15% for both intra- and inter-day variability. Drug recovery exceeded 98%, and stability tests demonstrated robustness under various conditions, with %CV values remaining under 15%. Pharmacokinetic studies in male Wistar rats (tadalafil: 0.0033 mg/kg; macitentan: 0.0003 mg/kg) revealed distinct absorption and elimination profiles. Tadalafil exhibited a peak concentration (Cmax) of 164.2 ng/mL at 1.5 h, an AUC0–t of 806 ng·h/mL, and a half-life of 5 h, indicative of rapid clearance. In contrast, macitentan displayed a lower Cmax of 43.8 ng/mL at 2 h, an AUC0–t of 987 ng·h/mL, and a prolonged half-life of 15 h, suggesting sustained systemic exposure. These pharmacokinetic variations highlight the potential for tailored dosing strategies. Environmental assessment using green analytical chemistry tools confirmed the eco-friendly design of the method, characterized by reduced solvent consumption and low toxicity. This validated LC-MS/MS method provides a robust and sustainable analytical solution for preclinical pharmacokinetic studies, delivering reliable data to inform safe and effective dosing of tadalafil and macitentan.